Analisis Perbandingan Penerapan Cash Basis dengan Accrual Basis dalam Penyusunan Laporan Keuangan Pemerintahan: Studi Kasus pada Satuan Kerja Direktorat Rumah Umum dan Komersial Kementrian Pekerjaan Umum dan Perumahan Rakyat - Dewi Nisa Amaliah; M. Nur Afif; Ayi Jamaludin Aziz (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
Presentation of government financial reports can be done on a cash basis and accrual basis. A qualitative descriptive method is used in this study. In this study, the author uses concepts in Government Accounting Standards (SAP), and is supported by the interview and documentation methods used. The focus of the research is recognition, recording and reporting. The study's findings demonstrate the disparities between the accrual and cash bases in the financial reports presented, such as in the cash basis there are 4 (four) financial report components such as the cash flow, balance sheet, and budget realisation report (LRA) Report (LAK) and Notes to the Report Finance (CaLK). Meanwhile, in the accrual basis there are 5 (five) components balance sheet, operational report (LO), budget realisation report (LRA), report on changes in equity (LPE), and notes to financial reports (CaLK) are the five types of financial reports. On the accrual basis, there is an Excess Operational Report (LO) and Budget Balance Report (SAL) which are not presented in the Report using a cash basis, in presenting the Report on Budget Realisation (LRA) it still uses a cash basis, while the Balance Sheet already uses an accrual basis.